The Imbalance Between Metalloproteinases and Their Tissue Inhibitors Is Involved in the Pathogenesis of Dermatitis Herpetiformis - Agnieszka Zebrowska; Joanna Narbutt; Anna Sysa-Jedrzejowska; Jozef Kobos; Elzbieta Waszczykowska (Hindawi Limited, 2005)
Dermatitis herpetiformis (DH) is a subepidermal autoimmune disease characterized by skin and intestinal lesions consistent with coeliac disease. There are also some data that metalloproteinases (MMPs) are involved in the development of skin lesions in DH, however their exact role in this process is not fully understood. The aim of the study was to investigate whether MMPs and their inhibitors are involved in pathogenesis of DH. Skin biopsies were taken from 13 patients with active DH and from 10 healthy subjects. The localization and expression of MMPs and TIMPs were examined by immunohistochemistry. MMPs expression was detected in basal keratinocytes and in the whole epidermis in all of the DH subjects. Neutrophils in microabscesses and in blister fluid were also positive for MMPs. Expression of TIMPs was moderate or weak in all examined biopsies. Our results allow us to conclude that imbalance between these enzymes takes an important role in the pathogenesis of DH.